PERAN SERTIFIKAT HALAL DALAM MENINGKATKAN PERTUMBUHAN EKONOMI SYARIAH DI INDONESIA - Latifah, Eny; Abdullah, Rudi (JIDE : Journal Of International Development Economics, 2022)
Halal certificates are seen as an identity that symbolizes the existence of halal in a product with the provisions of Islamic sharia. Its existence is often seen as a manifestation of sharia economic growth. This study aims to determine the extent of the role of halal product certification in increasing sharia economic growth in Indonesia. The method used is library research by collecting, analyzing and interpreting data sources originating from books, journals or other references with the aim of obtaining correct and correct information. The results of the study show that the role of halal product certification in sharia economic growth in Indonesia is: (1) halal certification becomes an instrument in the existing halal chain in the sharia economy in order to increase economic growth. (2) Halal certification is a driving force for Indonesia's achievements with the implementation of its sharia economic system, and (3) Halal certification has a role in increasing the quantity of economic growth in Indonesia because it is able to provide development support in the real industrial sector which is the main attraction for entrepreneurs.